Representasi Gender dan Agensi Perempuan dalam Diplomasi Budaya Korea Selatan: Kajian Feminis Atas K-Pop di Indonesia Tahun 2022-2023 (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
K-Pop has developed into a key instrument of South Korean cultural diplomacy with global reach, including in Indonesia. Behind its success as a soft power tool, K-Pop harbors complex dynamics of gender representation, particularly regarding the position and role of women. This study aims to analyze women's representation and agency in South Korean cultural diplomacy through K-Pop in Indonesia during the 2022–2023 period. This study uses a qualitative approach with a descriptive-interpretive design, combining a poststructuralist feminist perspective and cultural diplomacy theory. Data were collected through a documentary study of K-Pop cultural products and in-depth interviews with K-Pop fans in Indonesia. The results show that women play a central role in K-Pop's global success, both as idols and as active fans. However, women's representation in K-Pop is still dominated by standardized beauty standards and images of femininity. On the other hand, women's agency emerges through fandom practices that allow female fans to actively interpret, critique, and negotiate the meaning of gender representation. This study also found that gender issues have not been explicitly integrated into South Korean cultural diplomacy policies. These findings confirm that cultural diplomacy through K-Pop is dynamic and involves active interaction between the country, industry, and the recipient society.